Hi There, Can some one please help me with equation a bit rusty after after 15 years or so: 5x – 2 – 2x + 3=! Now thinking the answer is 3x + -1! Any help please
Follow Math Help Forum on Facebook and Google+
Originally Posted by squidge Hi There, Can some one please help me with equation a bit rusty after after 15 years or so: 5x – 2 – 2x + 3=! Now thinking the answer is 3x + -1! Any help please You are close: $\displaystyle 5x - 2 - 2x + 3$ $\displaystyle = (5x - 2x) + (-2 + 3)$ $\displaystyle = 3x + 1$ -Dan
View Tag Cloud